Shaping decision-making with screen time: video-based dialectical behavior therapy skills training for college students - Mejía, Diana; Avila-Chauvet, Laurent (Frontiers in Psychology, 2025)
IntroductionDialectical Behavior Therapy (DBT) is a transdiagnostic treatment that can address various mental health issues across diverse populations, including college students. However, a knowledge gap persists regarding how DBT might influence cognitive processes, particularly decision-making, through a brief intervention.MethodsThis study aimed to assess the effects of Video-DBT skills training on decision-making tasks among college students via an online platform. Ninety-five participants (comprising 50 men, 44 women, and one non-binary individual, age: M = 27.04, SD = 12.47) were randomly assigned to four core DBT skills groups. Participants received DBT training and underwent evaluation using three behavioral decision-making tasks: the Iowa Gambling Task (IGT), Delay Discounting (DD), and social discounting (SD).ResultsAlthough intriguing trends in discounting rates and IGT performance were observed among various groups before and after training, no statistically significant differences were found either among the groups or within individual groups. Nevertheless, it was discovered that distress tolerance and interpersonal effectiveness skills showed promise in reducing impulsivity and enhancing prosocial behavior.DiscussionThe findings highlight the potential of DBT skills training to influence cognitive and behavioral outcomes related to decision-making, even in the context of a brief teleintervention. While no statistically significant differences were observed, trends in discounting rates and IGT performance suggest that certain DBT skills, particularly distress tolerance and interpersonal effectiveness, may play a role in reducing impulsivity and fostering prosocial behavior.